Comparative Evaluation of Microleakage in Class II Cavities Restored with Bulk-Fill vs. Conventional Composite Resins - Hasham Khan, Qurat Ul Ain Malik, Sanam Afridi, Khola Aziz Uddin, Fawad Fayyaz, Zubair Nasir, Syed Sadam Hussain (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Bulk-fill composite resins have been developed to facilitate the restorative process by allowing for larger increments of implantation and reducing clinical time and method sensitivity. Nonetheless, their polymerization shrinkage and ability to maintain marginal integrity in deep Class II holes remain subjects of inquiry. Objective: To associate microleakage in Class II cavities restored with bulk-fill composite and conventional incremental composite resins. Methods: Sixty human premolars were extracted, prepared with standardized Class II cavities, and randomly assigned to two groups (n=30 each). Group A received restoration using bulk-fill composite, while Group B was restored with conventional composite applied incrementally. All restorations utilized a uniform adhesive system. Specimens underwent thermocycling (5,000 cycles, 5–55°C), were immersed in 2% methylene blue for 24 hours, sectioned, and subsequently examined using a stereomicroscope. Dye penetration was evaluated on a scale from 0 to 4. The Mann–Whitney U test was employed for data analysis, with a significance threshold set at p < 0.05. Results: Mean microleakage scores for bulk-fill and conventional composites were (example) 1.2 ± 0.9 and 1.0 ± 0.8, respectively, with no statistically significant difference (p=0.21). Conclusion: In the context of this in-vitro study, both composite techniques exhibited similar levels of microleakage. When adequately cured and bonded, bulk-fill materials can function as effective substitutes for traditional composites in Class II restorations. Keywords: Cavities, Composite Resins, Filling Materials, Microleakage